Sams teach yourself macromedia dreamweaver 4 in 24 hours - Bruce, Betsy (New Delhi : Techmedia, 2001)
In just 24 lessons of one hour or less, you will be up and running with Macromedia Dreamweaver 4. Using a straightforward, step-by-step approach, each lesson builds upon the previous one, allowing you to learn the essentials of Dreamweaver from the ground up. Use Dreamweaver to create basic Web pages with text and graphics. Create and apply templates. Create and image map. Design tables and use them for layout. Build frames and framesets. Add interactivity to your pages with Dynamic HTML. Make your site compatible with different browsers. Insert scripts and Dreamweaver actions into Web pages. Create a form with radio buttons, check boxes, lists, and menus. customize Dreamweaver to suit your specific needs.
Keywords: Web sites -- Authoring programs; Dreamweaver (Computer file).; Web site development